Study of characterization of natural biomaterials Nypa fruticans extract for scaffold fabrication using 3D bio-printing method - Darwin Hendri; Irwansyah Irwansyah; Arhami Arhami; M. Rizki Maulana; Aulia Indriani (Jurnal Polimesin, 2025)
Nypa fruticans (Arecaceae) is a tropical mangrove plant with potential as a natural biomaterial due to its galactomannan content, a water-soluble hetero-poly-saccharide suitable as a base material for bio-ink. This study aims to evaluate the potential of Nypa fruticans extract as a sustainable natural biomaterial for scaffold fabrication using 3D bio-printing technology. To optimize its mechanical and structural properties, glycerol and sorbitol were added as plasticizing agents. The research methods consist of (a) maceration method extraction of Nypa fruticans fruit, subsequent characterization by Fourier Transform Infrared (FTIR) spectroscopy and Gas Chromatography-Mass Spectrometry (GCâ€“MS) analysis, (b) formulation of biomaterials with glycerol and sorbitol at varying concentrations (5%, 10%, and 15%), and (c) scaffold fabrication using 3D bio-printing. The scaffolds were then assessed for printed line width, density, and porosity. FTIR analysis confirmed the presence of hydroxyl (Oâ€“H) functional groups at 3600â€“3300 cmâ»Â¹, while GCâ€“MS detected 5-hydroxymethylfurfural, indicating polysaccharide derivatives consistent with galactomannan content. The addition of sorbitol significantly influenced the physical properties and printability of the formulated bio-ink, with the optimal composition obtained at 85% Nypa fruticans extract and 15% sorbitol. This formulation successfully produced stable CAD-based scaffold architectures with cubic and rhombic pore configurations, achieving precise deposition widths (Â±1.18 mm) relative to the 0.5-mm nozzle diameter. An increased sorbitol concentration of 15% correlated with higher scaffold density (up to 0.971 g/cm3) and reduced porosity (down to 0.436). These findings demonstrate the potential of Nypa fruticans extract as an efficient and sustainable natural bio-ink for tissue engineering applications.Study of characterization of natural biomaterials Nypa fruticans extract for scaffold fabrication using 3D bio-printing method